Abdominal vagus nerve stimulation as a new therapeutic approach to prevent postoperative ileus. Issue 9 (21st April 2017) - Stakenborg, N.; Wolthuis, A. M.; Gomez‐Pinilla, P. J.; Farro, G.; Di Giovangiulio, M.; Bosmans, G.; Labeeuw, E.; Verhaegen, M.; Depoortere, I.; D'Hoore, A.; Matteoli, G.; Boeckxstaens, G. E.
Abstract: Background: Electrical stimulation of the cervical vagus nerve (VNS) prevents postoperative ileus (POI) in mice. As this approach requires an additional cervical procedure, we explored the possibility of peroperative abdominal VNS in mice and human. Methods: The effect of cervical and abdominal VNS was studied in a murine model of POI and lipopolysaccharide (LPS)‐induced sepsis. Postoperative ileus was quantified by assessment of intestinal transit of fluorescent dextran expressed as geometric center (GC). Next, the effect of cervical and abdominal VNS on heart rate was determined in eight Landrace pigs to select the optimal electrode for VNS in human. Finally, the effect of sham or abdominal VNS on LPS‐induced cytokine production of whole blood was studied in patients undergoing colorectal surgery. Key Results: Similar to cervical VNS, abdominal VNS significantly decreased LPS‐induced serum tumor necrosis factor‐α (TNFα) levels (abdominal VNS: 366±33 pg/mL vs sham: 822±105 pg/mL; P <.01). In line, in a murine model of POI, abdominal VNS significantly improved intestinal transit (GC: sham 5.1±0.2 vs abdominal VNS: 7.8±0.6; P <.01) and reduced intestinal inflammation (abdominal VNS: 35±7 vs sham: 80±8 myeloperoxidase positive cells/field; P <.05). In pigs, heart rate was reduced by cervical VNS but not by abdominal VNS. In humans, abdominal VNS significantly reduced LPS‐induced IL8 and IL6 production by whole blood. Conclusions & Inferences: Abdominal VNS is feasible and safe in humans and has anti‐inflammatory properties. As abdominal VNS improves POI similar to cervical VNS in mice, our data indicate that peroperative abdominal VNS may represent a novel approach to shorten POI in man. Abstract : Vagus nerve stimulation (VNS) has anti‐inflammatory effects in immune‐mediated disorders such as sepsis and postoperative ileus. Traditionally, VNS has always been performed at cervical level. In this article, we evaluated the anti‐inflammatory properties of abdominal VNS in sepsis and postoperative ileus, thus avoiding additional incisions in the neck.